PENGATURAN HUKUM TOKO MODERN WARALABA TERHADAP EKSISTENSI PASAR TRADISIONAL DI KOTA DENPASAR - Citra, Made Emy Andayani; Wijana, I Wayan (Jurnal Advokasi, 2015)
Basiclly that the rules that apply to franchise agreements (franchisting) in Indonesia is the norm of a special presence to set the franchise stipulated in Government Regulation No. 42 Year 2007 on Franchise and Minister of Trade Regulation No.68 / M - DAG / PER / 10 / year 2012 on franchise Business Type modern Store as well as other regulations related adjusted by the Regional Regulation modern stores where the franchise was founded.               Existence of traditional markets in the city of Denpasar is still maintained and not altered by the presence of modern shop franchise and it does not bias is inevitable given the people of Bali itself, which is predominantly Hindu, where many needs that require a person to shop at traditional markets, automatically it becomes value more for the traditional market .